Analisis Efisiensi Pemompaan pada Miniatur Pompa Hidram dengan Letak Katup Pengantar dan Katup Limbah yang Berbeda - Sakaria Koli; Muhamad Jafri; Ishak S. Limbong (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2014)
Water is major need for an inseparable of human society. One of the efforts to obtain water continuously is with the pump methods. From the several types of pumps are widely used, the hydram pump is one of the solution because it does not use fuel. The aim of this research is to find out the influence of different position between waste valve and impulse valve to the pump efficiency. All units miniature hydram pump which used in this research, have same size. In testing, any units treated with the same high of water fall is 1 meter, the high length of inlet pipe is 2.3 meter, the diameter of a pipe in is 16 millimeter, the diameter of a pipe out is 6,35 millimeter and the weight of waste valve is 42 grams. Testing performed on variations of the waste valve step length (5 millimeter, 10 millimeter, 15 millimeter, 20 millimeter and 25 millimeter) and at high raise (6 meter and 10 meter). The result showed that for the second arrangements, any additional length of a stride, the efficiency with which produced tends to decline it is caused by a distance step of the waste valve. The more distant make the waste valve the time it takes to shut down a little longer. So as to discharge water wasted become bigger. High lift, for variations on high lift 10 m and the arrangement of a inlet pipe-waste valve -delivery valve efficiency greater at 55,934 %, and on high lift 6 meter the efficiency with which produced reached 40,265 %. It was happened because the potential and kinetic energy are used to push valve waste firstly, so the valve closed faster and quantity of water that flow from the valve is less.